Factors leading to customer retention in the high volume-low volume service context: Evidence from the mobile service industry - Cheng, Boon Liat *; Gaur, Sanjaya S.; Rezuan, Abdul Rahim (MAG Scholar, 2020)
Service convenience has undoubtedly gain substantial recognition for both goods and service industries within recent years towards forging an enduring competitive advantage. Considering heightened market expectations in the mobile service industry, importance of capitalizing on relevant elements is highlighted to retain, further strengthen users’ loyalty. Technological advancement has then created opportunity for differentiation in the area of reachability, particularly on the transaction convenience and access convenience of specified mobile service. Alongside product involvement, brand image and perceived value as hypothesized predictors of users’ allegiance towards a mobile service, this study explored factors which influence customers’ loyalty and propensity to leave within the mobile service industry. Convenience sampling approach was hereby implemented, following distribution of close-ended questionnaires among 400 respondents. Data analysis was then conducted through employment of the SEM AMOS software. As such, results obtained discovered product involvement, perceived value, transaction convenience and access convenience being direct predictors of both dependent variables; with the exception of brand image which doesn’t affect propensity to leave, despite being a significant antecedent to customers’ loyalty. Additionally, transaction convenience was revealed as an active moderator to the impact of perceived value on (i) customer loyalty, and (ii) propensity to leave. Centred on the transactional aspect in the mobile service industry, more effective service marketing strategies can be developed through gained insights from this research, with excelling sustainable customer retentions.